Standards and Methodological Rigor in Pulmonary Arterial Hypertension Preclinical and Translational Research. Issue 7 (30th March 2018) - Provencher, Steeve; Archer, Stephen L.; Ramirez, F. Daniel; Hibbert, Benjamin; Paulin, Roxane; Boucherat, Olivier; Lacasse, Yves; Bonnet, Sébastien
Abstract : Despite advances in our understanding of the pathophysiology and the management of pulmonary arterial hypertension (PAH), significant therapeutic gaps remain for this devastating disease. Yet, few innovative therapies beyond the traditional pathways of endothelial dysfunction have reached clinical trial phases in PAH. Although there are inherent limitations of the currently available models of PAH, the leaky pipeline of innovative therapies relates, in part, to flawed preclinical research methodology, including lack of rigour in trial design, incomplete invasive hemodynamic assessment, and lack of careful translational studies that replicate randomized controlled trials in humans with attention to adverse effects and benefits. Rigorous methodology should include the use of prespecified eligibility criteria, sample sizes that permit valid statistical analysis, randomization, blinded assessment of standardized outcomes, and transparent reporting of results. Better design and implementation of preclinical studies can minimize inherent flaws in the models of PAH, reduce the risk of bias, and enhance external validity and our ability to distinguish truly promising therapies form many false-positive or overstated leads. Ideally, preclinical studies should use advanced imaging, study several preclinical pulmonary hypertension models, or correlate rodent and human findings and consider the fate of the right ventricle, which is the major determinant of prognosis in human PAH. Although these principles are widely endorsed, empirical evidence suggests that such rigor is often lacking in pulmonary hypertension preclinical research. The present article discusses the pitfalls in the design of preclinical pulmonary hypertension trials and discusses opportunities to create preclinical trials with improved predictive value in guiding early-phase drug development in patients with PAH, which will need support not only from researchers, peer reviewers, and editors but also from academic institutions, funding agencies, and animal ethics authorities.